2012
DOI: 10.1186/1743-422x-9-69
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 replication with stable RNAi-mediated knockdown of autophagy factors

Abstract: Autophagy is a cellular process leading to the degradation of cytoplasmic components such as organelles and intracellular pathogens. It has been shown that HIV-1 relies on several components of the autophagy pathway for its replication, but the virus also blocks late steps of autophagy to prevent its degradation. We generated stable knockdown T cell lines for 12 autophagy factors and analyzed the impact on HIV-1 replication. RNAi-mediated knockdown of 5 autophagy factors resulted in inhibition of HIV-1 replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…24 Depending on cell type, the effect of HIV-1 on autophagy varies with the course of productive infection or bystander effect of viral proteins. Although autophagy proteins are required for virus replication in CD4 C T lymphocytes, 43 the autophagy process is reported to restrict HIV infection in these cells. Recently Sagnier et al report inhibition of virus replication in CD4 C T cells by autophagymediated degradation of Tat.…”
Section: Discussionmentioning
confidence: 99%
“…24 Depending on cell type, the effect of HIV-1 on autophagy varies with the course of productive infection or bystander effect of viral proteins. Although autophagy proteins are required for virus replication in CD4 C T lymphocytes, 43 the autophagy process is reported to restrict HIV infection in these cells. Recently Sagnier et al report inhibition of virus replication in CD4 C T cells by autophagymediated degradation of Tat.…”
Section: Discussionmentioning
confidence: 99%
“…(Nardacci et al, 2014) However, it has also been shown that knockdown of autophagy factors in T-cell lines can inhibit HIV replication. (Eekels et al, 2012) Certainly there is a complex relationship between HIV and autophagy, and the nature of the interactions between virus and pathway depend on the cell and the circumstances. This may be true for most viruses, which are often studied in easy-to-grow cell lines.…”
Section: The Complex Relationship Between Hiv and Autophagymentioning
confidence: 99%
“…This LC3 isoform is cleaved as the cytoplasmic LC3-I form, which, upon induction of autophagy, is linked to phosphatidylethanolamine at its C terminus and is associated with the autophagosomal membrane as the LC3-II form (38,39). In recent years, several studies have demonstrated the implications of autophagy in virus replication (40)(41)(42) and, more specifically, in HIV-1 infection and pathogenesis (43)(44)(45)(46)(47)(48)(49). In T cells, HIV-1-induced autophagy has been suggested to depend on the surface expression of Env proteins, leading to apoptosis of infected and uninfected CD4 ϩ T cells (43,45,46,50).…”
mentioning
confidence: 99%